2007
DOI: 10.1016/j.neulet.2007.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Neuroexcitatory actions of Tamiflu and its carboxylate metabolite

Abstract: Oseltamivir (Tamiflu) is now being stockpiled by several governments as a first line treatment for an anticipated outbreak of avian influenza caused by H5N1. However, abnormal behaviors and death associated with the use of Tamiflu have developed into a major issue in Japan where Tamiflu is often prescribed for seasonal influenza. Thus, it is critical to determine neuropsychiatric effects of oseltamivir and to establish methods for safe administration. Using juvenile rats and rat hippocampal slices, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
86
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 21 publications
5
86
1
Order By: Relevance
“…following non-sedating dose of ethanol injection in rats significantly altered the duration of loss of lightning reflex [59]. They also reported diminished behavioral activity and poor locomotion by measuring the number of arm entries in the Y-maze, representing a form of anxious or fearful behavior as manifest by altered exploration [60].…”
Section: Toxicity and Toxicokinetics Studies In Juvenile Rats: An mentioning
confidence: 99%
See 4 more Smart Citations
“…following non-sedating dose of ethanol injection in rats significantly altered the duration of loss of lightning reflex [59]. They also reported diminished behavioral activity and poor locomotion by measuring the number of arm entries in the Y-maze, representing a form of anxious or fearful behavior as manifest by altered exploration [60].…”
Section: Toxicity and Toxicokinetics Studies In Juvenile Rats: An mentioning
confidence: 99%
“…Ethanol injection in the presence of oseltamivir also resulted in enhanced hypothermia. [59]. Izumi et al also reported that combination of oseltamivir with other neurostimulants altered synaptic plasticity and this may contribute to behavioural changes associated with the drug [60].…”
Section: Toxicity and Toxicokinetics Studies In Juvenile Rats: An mentioning
confidence: 99%
See 3 more Smart Citations